Convalescence in the nineteenth-century novel - Krienke, Hosanna (Cambridge University Press, 2021)
Victorian Britain witnessed a resurgence of traditional convalescent caregiving. In the face of a hectic modern existence, nineteenth-century thinkers argued that all medical patients desperately required a lengthy, meandering period of recovery. Various reformers worked to extend the benefits of holistic recuperative care to seemingly unlikely groups: working-class hospital patients, insane asylum inmates, even low-ranking soldiers across the British Empire. Hosanna Krienke offers the first sustained scholarly assessment of nineteenth-century convalescent culture, revealing how interpersonal post-acute care was touted as a critical supplement to modern scientific medicine. As a method of caregiving intended to alleviate both physical and social ills, convalescence united patients of disparate social classes, disease categories, and degrees of impairment. Ultimately, this study demonstrates how novels from Bleak House to The Secret Garden draw on the unhurried timescale of convalescence as an ethical paradigm, training readers to value unfolding narratives apart from their ultimate resolutions.
10.1017/9781108953788
Keywords: English fiction; Literature and medicine; Health in literature; Care of the sick in literature